DAMPAK PERTUMBUHAN PENDUDUK TERHADAP LINGKUNGAN DAN BUDAYA SUBAK : STUDI KASUS DI KABUPATEN TABANAN PROVINSI BALI - I Nyoman Wardi; I.A Alit Laksmiwati; I Gusti Alit Gunadi; Abd Rahman As-syakur (Bumi Lestari Journal of Environment, 2014)
The research aims to reveal the trens population growth over the 10 years (2002-2012) inTabanan Regency, as well as their impact on the land conversion of subak as well as otherchanges in environmental and cultural aspects of subak. Research conducted through thestages of data collection and data analysis. The technique of data collection was done bythe library research, observation, and structured interviews with questionnaires and indepthinterviews (depth interview).The data collected was analyzed by descriptivequalitativeand quantitative analysis with the help of cross-tables and analysis of satelliteimagery.Resultsof the study showed, the number of inhabitants of TabananRegency in 2012 reached441.900people, consisting of 220. 002-sex guy men and 221.898 women. The livelihoods ofinhabitants,mostly working in the agricultural sector (110.449people) and plantations(45,326people). Based on analysis conducted, it was revealed that within the last 10 years(2002-2012)population growthreached26,10% or = 2.61% per year.The highest growthoccurredin the district of Kediri 5,76%, then followed by district of  Baturiti 5.13%, Marga4.05%,and district of  Tabanan,3,69%. The lowest population growthoccurredin districtPenebel0.34%, then followed by the district of Kerambitan 0,56% and district of EastSelemadeg0.82%. The population growth seems to be more of a factor caused by migration(peoplecoming) 62,24% (1294 inhabitants) (from the difference in population that comes3293with people out 1999 inhabitants), if compared with population growth naturallyonlyachieve 37,76% (785 inhabitants).Thepopulation growth indirectly affects the occurrence of changes in the environment andcultureof subak. In the past 10 years occurred the shrinking land subak (fields) 672,89 ha,or2.95% of the total area of paddy fields in 2002 (22.842 fare ha). Other environmentaleffects,i.e. reduced water supply and the breakdown in some irrigation farmers, pollutionandthe impact of irrigation channel blockage by garbage plastic and aesthetic degradationofthe environment. Socio-cultural impact of subak, which tendency to the occurrence ofsocialconflict, disruption in the silent  ritual of rice fields (penyepian carik) and theabandonment of cultural heritage (pura subak) due to the occurrence of function fields intohousing and tourism facilities.The protection needs to be done to the environment and subak culture through the populationgrowth control with government policy, the formulation of customary law of subak (awigawig),and improve the welfare of farmers through the development of ecotourism that basedonsubak ecosystem.